2021
DOI: 10.1016/j.adro.2021.100724
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Work–Life Integration Among Medical Physicists

Abstract: To generate an understanding of the primary concerns facing medical physicists regarding integration of a demanding technical career with their personal lives. Methods and Materials: In 2019, we recruited 32 medical physics residents, faculty, and staff via emails to US medical physics residency program directors to participate in a 1-hour, semistructured interview that elicited their thoughts on several topics, including work−life integration. Standard techniques of qualitative thematic analysis were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…racial/ethnic minoritized populations, sexual and gender minorities, disabled populations, and others) face additional challenges and discrimination that compound these effects. 14 , 35 , 36 Most residency programs currently participate in the MedPhys Match program, administered by National Matching Services Inc., with the match rate hovering around 60% over the past three years. In 2020, the average number of positions ranked per matched applicant was 8.9 (prior to the coronavirus disease 2019 [COVID‐19] pandemic when interviews were primarily conducted in‐person), illustrating some of the expense and stress, both for applicants and programs, associated with the residency interview period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…racial/ethnic minoritized populations, sexual and gender minorities, disabled populations, and others) face additional challenges and discrimination that compound these effects. 14 , 35 , 36 Most residency programs currently participate in the MedPhys Match program, administered by National Matching Services Inc., with the match rate hovering around 60% over the past three years. In 2020, the average number of positions ranked per matched applicant was 8.9 (prior to the coronavirus disease 2019 [COVID‐19] pandemic when interviews were primarily conducted in‐person), illustrating some of the expense and stress, both for applicants and programs, associated with the residency interview period.…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the University of Michigan Institutional Review Board. A detailed description of the methods used in this study may be found in Paradis et al 14 Our study team consisted of an MP trained in qualitative methods (Kelly C Paradis), a radiation oncologist with a doctorate in social science (Reshma Jagsi), a senior research assistant/sociologist with experience as a qualitative interviewer, facilitator, and data analysis (Kerry A Ryan), an undergraduate research assistant trained in qualitative methods (Spencer Schmid), and additional MPs and radiation oncologists who provided contributions to study design and data interpretation (Jean M Moran,Anna Laucis,Christina H Chapman,Terri Bott-Kothari, Joann I Prisciandaro, Samantha Simiele, James M Balter, Martha M Matuszak, and Vrinda Narayana). Briefly, from February to May of 2019, we recruited 32 practicing MPs and MPRs from across the US to participate in confidential, 1-h, semi-structured interviews on the topics of work/life integration, mentorship, and discrimination within the field of medical physics.…”
Section: Methodsmentioning
confidence: 99%
“…Important research and advocacy is being performed outside of the United States and by other members of the healthcare team including physicists, and others that could not be adequately reviewed in the scope of this article. 5,58 All people benefit from intentional promotion of gender equity and diversity through enhanced productivity, 59 policy change, 25 and improved patient outcomes, 11,60 Tables are a compilation of select recent and relevant resources for interested individuals and leaders seeking to support gender equity. As a professional field, we must commit to implementing change, which promotes gender equity and eliminates detrimental gendered expectations.…”
Section: Inequity In Salarymentioning
confidence: 99%
“…Important research and advocacy are being performed outside of the United States and by other members of the health care team, including physicists and others, that could not be adequately reviewed in the scope of this article. 5 , 58 …”
Section: Underrepresentation In Leadershipmentioning
confidence: 99%
“…Small but essential actions address childcare responsibilities and improve young women’s participation in conferences. For example, in a qualitative study with medical physics residency program directors [ 12 ], many participants cited the new childcare offering at the annual AAPM meeting as a positive step in helping more women physicists have the opportunity to attend this meeting.…”
Section: The Presentmentioning
confidence: 99%